Energy Efficiency in Rent Seeking Economies:Is Credit Capable of Breaking the Energy Curse? - Burakov, Dmitry (International Journal of Energy Economics and Policy, 2015)
In this article, we set ourselves a task of determining a potential of using credit for improving energy efficiency in the economy of rent seeking. Based on cross-country analysis and using channels’ approach to estimation of institutions’ and market’s efficiency we come to conclusion that persistently low energy efficiency in East European countries may be a result of low quality market institutions. Testing a hypothesis of credit being the source of improving energy efficiency (e.g., through introduction and granting energy efficient loans) showed that the effect of credit channel is negative in case of low quality institutions in the economy and low elasticity of national markets. On opposite, credit is capable of breaking the energy curse, when successful institutional infrastructure is functioning, and competitive environment takes its place when geographical and spatial features are taken into account. Keywords: energy efficiency; rent seeking; credit market. JEL Classifications: E02; G21; O13; Q43